2005
DOI: 10.1002/ca.20114
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic pattern of the terminal branches of posterior interosseous nerve

Abstract: To understand the lesion of the terminal branches of posterior interosseous nerve (PIN), an anatomic study was carried out. Thirty adult cadaver arms were dissected and the anatomic pattern of the nerve was documented. The distance between the point at which the nerve divides into branches and the distal edge of the supinator were measured, as well as the length of each nerve branch to its muscle-entering sites. The number of branches innervating each muscle was recorded. It was found that the PIN was branchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
(30 reference statements)
1
19
0
1
Order By: Relevance
“…The anatomy of the PIN in the proximal forearm has been well described in the past, with multiple authors describing the location of branches to the various muscles supplied by the PIN (Prasartritha et al, 1993;Abrams et al, 1997;Branovacki et al, 1998;Ozkan et al, 1999;Ebraheim et al, 2000;Seradge et al, 2000;Thomas et al, 2000;Ay et al, 2005;Tubbs et al, 2006;Hazani et al, 2008;Artico et al, 2009;Bertelli et al, 2009). It has also been shown that pronation of the forearm increases the distance between the PIN and the surgical approach when the posterior approach is used to expose the proximal radius (Strachan and Ellis, 1971;Tornetta et al, 1997;Witt and Kamineni, 1998;Diliberti et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The anatomy of the PIN in the proximal forearm has been well described in the past, with multiple authors describing the location of branches to the various muscles supplied by the PIN (Prasartritha et al, 1993;Abrams et al, 1997;Branovacki et al, 1998;Ozkan et al, 1999;Ebraheim et al, 2000;Seradge et al, 2000;Thomas et al, 2000;Ay et al, 2005;Tubbs et al, 2006;Hazani et al, 2008;Artico et al, 2009;Bertelli et al, 2009). It has also been shown that pronation of the forearm increases the distance between the PIN and the surgical approach when the posterior approach is used to expose the proximal radius (Strachan and Ellis, 1971;Tornetta et al, 1997;Witt and Kamineni, 1998;Diliberti et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…We found high variability of the innervation of the supinator by the PIN, with up to nine nerve branches supplying the muscle, and 25% of the specimens were classified as high risk of injury of the nerve supply to the supinator, or in one case, of PIN injury during a posterior exposure of the biceps tuberosity. Abrams et al (1997) found a mean of 3.9 branches to the supinator in a study of 20 cadavers, and Ay et al (2005) as well as Branovacki et al (1998) described significant variability in the innervation of the supinator. Bertelli et al (2009) described variable innervation of the supinator with the most common pattern consisting of two main branches originating from the PIN at an average of 12 and 17 mm proximal to the arcade of Frohse.…”
Section: Discussionmentioning
confidence: 95%
“…A variant deep branch such as this may produce only partial loss of ulnar motor function (Auerbach et al 1994). This variation should also be considered when performing decompression of Guyon's canal or excision of an ununited hook of the hamate (Ay et al 2005;Aydinlioglu et al 2010).…”
Section: Targetsmentioning
confidence: 99%
“…The order of motor branches from the radial and posterior interosseous nerve in the forearm, from proximal to distal, is most commonly brachialis, extensor carpi radialis longus, supinator, extensor carpi radialis brevis, extensor digitorum communis, extensor carpi ulnaris, extensor digiti minimi, abductor pollicis longus, extensor pollicis longus, extensor pollicis brevis, and extensor indicis proprius; this order is however quite variable (Sunderland 1946;Spinner 1978;Abrams et al 1997;Doyle and Botte 2003;Ay et al 2005). For example, the brachioradialis may rarely receive a branch prior to those to brachialis.…”
Section: Targetsmentioning
confidence: 99%
“…Bu sinirin hasarında ise düşük başparmak ve/veya parmak paralizileri ortaya çıkabilmektedir. 9 MAPL, os metacarpale I'e tutunduğu için baş-parmağın stabilizasyonunda, elin fonksiyonunda, özellikle de tenosinovit ve başparmak metakarp kı-rıklarında önemli rol oynamaktadır. Örneğin baş-parmak metakarp bazisinin kırıklarında MAPL'nin, kırığın bir parçasının yerini değiştirerek art.…”
unclassified